Character Education Development with Literature: Introducing Intercultural Character Model (ICM) in English Learning through English Literature at Indonesian’s International Islamic Senior High School Students. - Juliastuti; Palu, Fitriningsih (ISTIQRA: Jurnal Hasil Penelitian, 2021)
Multicultural is like two blades, one side make our nation rich in cultural treasures, but on the other hand, is prone to cause conflicts, disputes and conflict. One of the efforts to strengthen national resilience is developing character education. Implementation of character education through intercultural understanding must see three aspects namely: paradigm shift, material education and learning methods. One way to bring character education into a solid curriculum is to make it part of the language program by instilling character learning through reading and language arts through high quality literature. As an international class representation of the scope of the department of religion that produces religious students and masters science and technology (IPTEKS) Madrasah Aliyah Negeri Insan Cendikia (MAN IC) Palu, South Sulawesi, Indonesia was chosen as a place to conduct research in character development interculturalists through teaching literary works both in learning English (as a foreign language or English as Foreign Language / EFL). This study uses a questionnaire based inquiry approach to the statistical survey method in three different sample groups of students. The group of students that became the sample covered a different age range aged 13-15 years in three groups. After the introduction of numbers in ten questions about whether students and the public need literary works in English to get to know the culture of the target language and to know the intercultural character, the number obtained is 100% YES. The values contained in English literature are the highest choices of the three groups namely strength of character (heroic), honest and truth. The second highest reason chosen was due to aesthetic or beauty. In the interview session heroic literary works (action) occupy the highest number of literary works of their choice. In contrast, values, opinions and perspectives, among cultures, are not represented. It is concluded that Intercultural Character Model very much needed.